Muka positif dan muka negatif teori Brown dan Levinson dalam novel “Seribu Wajah Ayah” karya Azhar Nurun Ala - Anggraini, Novia Retnowati (Maliki Interdisciplinary Journal, 2024)
One form of literary work expressed through language is the novel. A novel is an essay or work of imagination that tells a story about social problems or social life. The literary work in question is the novel "Seribu Wajah Ayah" by Azhar Nurun Ala. The aim of this research is to analyze the politeness of positive faces and negative faces in the dialogue of the novel "Seribu Wajah Ayah" by Azhar Nurun Ala. This research uses a qualitative descriptive method, using reading and note-taking techniques. The researcher read the novel "Seribu Wajah Ayah" carefully, then recorded the appropriate data results. So in this study it can be concluded that 7 data were found, 4 data were in the form of positive facial politeness, and the other 3 were negative facial politeness.